2016
DOI: 10.3389/fpsyg.2016.00592
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Trait Related Theory of Mind Impairment in First Episode Psychosis Patients and Its Relationship with Processing Speed: A 3 Year Follow-up Study

Abstract: This study aimed to confirm whether first-episode psychosis patients present a stable trait impairment in theory of mind (ToM) and to examine the potential relationship between ToM and clinical symptomatology and neurocognition. Patients with a first episode of psychosis (N = 160) and healthy controls (N = 159) were assessed with an extensive neuropsychological test battery, which included a mental state decoding task known as “The Reading the Mind in the Eyes” (Eyes test), at baseline and reassessed after 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
2
24
1
Order By: Relevance
“…Therefore, ToM functions are less likely to be considered as a trait marker of schizophrenia. The findings of our study seem to stand at odds with the results of Ayesa-Arriola et al [26] who found stable RMET performances in psychosis over a 3-year follow-up period. There are several differences between the studies that can explain the seemingly discrepant findings.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Therefore, ToM functions are less likely to be considered as a trait marker of schizophrenia. The findings of our study seem to stand at odds with the results of Ayesa-Arriola et al [26] who found stable RMET performances in psychosis over a 3-year follow-up period. There are several differences between the studies that can explain the seemingly discrepant findings.…”
Section: Discussioncontrasting
confidence: 99%
“…There are several differences between the studies that can explain the seemingly discrepant findings. First, in our study, the follow-up period was longer, but the sample size was smaller as compared to the study of Ayesa-Arriola et al [26]. Second, Ayesa-Arriola et al [26] included first-episode patients with psychosis, whereas our sample consisted of more chronic cases with schizophrenia.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The former correlation may suggest a potential role of years of education as a moderator factor of ToM abilities, especially for the affective subcomponent, as also demonstrated in studies performed in healthy populations that examined ET performances in relation to some demographic variables, including years of education (Fernández-Abascal et al, 2013; Ayesa-Arriola et al, 2016). In this regard, our results, although deserving further investigation because only correlational and not causal, may support the notion that education could influence and improve social cognition, thus encouraging the use of training programs, as demonstrated in other neuropsychiatric conditions (Rocha and Queirós, 2013; Sacks et al, 2013).…”
Section: Discussionmentioning
confidence: 61%